Alkalinity regulation in calcium carbonate‐buffered lakes. (19th October 2015) - Müller, Beat; Meyer, Joseph S.; Gächter, René
Abstract: Biogenic calcite precipitation is the removal of calcite (CaCO3 ) from the epilimnion to the sediments of hard‐water lakes during summer stratification, caused by increased pH during algal blooms and by nucleation of calcite crystals on surfaces of micro‐algae. Although this phenomenon has been studied for decades, details of the underlying mechanisms are still debated. Using results of approximately 70, 000 alkalinity measurements from 13 hard‐water Swiss lakes (each with approximately 30 yr to 50 yr of monitoring), we demonstrate that (i) calcium carbonate‐buffered lakes act as alkalinity sinks during summer stratification but act as CO2 sources during and immediately after spring overturn; (ii) as the alkalinity concentration ([Alkmix ]) and the total phosphorus concentration ([TPmix ]) at spring overturn increase, increasingly more alkalinity is lost from the epilimnion during summer stratification; (iii) [Alkmix ] is determined by the lake's discharge‐weighted average inflow concentration ([Alkin ]), flushing rate, mean depth and [TPmix ]; and (iv) [Alkin ] depends on the mineralogy and the land use affecting in‐soil nitrification of ammonia and subsequent calcite dissolution in the catchment.